Table of Contents
There are various student are search formula of (a-b)^3 and a^3-b^3. Now I am going to explain everything below. You can check and revert back if you like. you can also check cube formula in algebra formula sheet.
- a2 – b2 = (a – b)(a + b)
- (a+b)2 = a2 + 2ab + b2
- a2 + b2 = (a – b)2 + 2ab
- (a – b)2 = a2 – 2ab + b2
- (a + b + c)2 = a2 + b2 + c2 + 2ab + 2ac + 2bc
- (a – b – c)2 = a2 + b2 + c2 – 2ab – 2ac + 2bc
- (a + b)3 = a3 + 3a2b + 3ab2 + b3 ; (a + b)3 = a3 + b3 + 3ab(a + b)
- (a – b)3 = a3 – 3a2b + 3ab2 – b3
- a3 – b3 = (a – b)(a2 + ab + b2)
- a3 + b3 = (a + b)(a2 – ab + b2)
- (a + b)3 = a3 + 3a2b + 3ab2 + b3
- (a – b)3 = a3 – 3a2b + 3ab2 – b3
- (a + b – c)2 = a2 + b2 + c2 + 2ab – 2bc – 2ca
- (a – b + c)2 = a2 + b2 + c2 – 2ab – 2bc + 2ca
- (a – b – c)2 = a2 + b2 + c2 – 2ab + 2bc – 2ca
- (a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca
- a^2 – b^2 = (a – b)(a + b)
- (a+b)^2 = a^2 + 2ab + b^2
- a^2 + b^2 = (a – b)^2 + 2ab
- (a – b)^2 = a^2 – 2ab + b^2
- (a + b + c)^2 = a^2 + b^2 + c^2 + 2ab + 2ac + 2bc
- (a – b – c)^2 = a^2 + b^2 + c^2 – 2ab – 2ac + 2bc
- (a + b)^3 = a^3 + 3a^2b + 3ab^2 + b3
- (a + b)^3 = a^3 + b^3 + 3ab(a + b)
- (a – b)^3 = a^3 – 3a^2b + 3ab^2 – b^3
- a^3 – b^3 = (a – b)(a^2 + ab + b^2)
- a^3 + b^3 = (a + b)(a^2 – ab + b^2)
- (a + b)^3 = a^3 + 3a^2b + 3ab^2 + b^3
- (a – b)^3 = a^3 – 3a^2b + 3ab^2 – b^3